Incorporating Arts into Electronics Engineering: A STEAM Approach to an Embedded Systems Programming Course - Kertész, Csaba Zoltán (MDPI, 2025)
The growing demand for electronics engineers is one of the cornerstones of STEM education. Recent trends in education show an extension of the STEM principle into STEAM by mixing Arts with the traditional Science, Technology, Engineering, and Math disciplines. Especially in elementary education, this has beneficial effects by increasing the appeal of STEM disciplines. This STEAM principle is less studied in university settings, but it can be beneficial for engineering students as well. This paper presents a case study of extending an Embedded Systems Programming class to include GUI design elements. Employing graphical user interfaces in embedded devices has been an increasing trend in the last decade, and there is also demand for introducing it into courses concerning embedded systems and microcontrollers. Teaching engineering students about graphic design has two main benefits: it increases the appeal of the course and also leads to better understanding the interaction between the two worlds of Arts and Engineering. The survey results of students after finishing the course show a high satisfaction level.
Keywords: STEAM education; Embedded Systems Programming; GUI design